ANALISIS PENGARUH INFLASI DAN PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN - Lubis, Delima Sari (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2017)
One of the problems being going developing countries is unemployment. Unemployment is a quite complicated problem and requires seriousness in solving it. If economic growth increases it will cause unemployment to decline. The result of research shows that partially variable of inflation does not have significant effect to unemployment.It is based by  tcount (-0.147921 ttable( 2.01537. While the economic growth variable has no effect on unemployment. The t test shows the obtained tcount(-0.369640)ttable (2.01537). Simultaneously, the variables of inflation, economic growth and dummy variables have an effect on unemployment cause Fcount(7.101933) Ftable(2.82). The determination coefficient test is 0.509637,  It indicates that the independent variables are able to explain the dependent variable of 50.9 percent, while the 49.1 percent is influenced by other variables outside of this research. The research equation that  isPG = 17.43638+(-0.014508*INF)–(0.240327*PE)+(-5.072613*DUMMY)+ eit.Keywords: Inflation, Economic Growth, Unemployment